Fashion and art - Geczy, Adam.; Karaminas, Vicki (London Berg, 2012)
Bringing together original, cutting-edge contributions from leading international scholars across a range of disciplines, this book is essential reading for anyone interested in exploring the intersections and changing relationship between fashion and art, past and present.
Introduction: Adam Geczy and Vicki Karaminas -- 1. Fashion: Valerie Steele, The Museum at the Fashion Institute of Technology, USA -- 2. Art: Nancy Troy, Stanford University, USA -- 3. Aesthetics: Llewellyn Negrin, University of Tasmania, Australia -- 4. Modernity: Adam Geczy, Sydney College of the Arts, Australia -- 5. Conceptual: Hazel Clark, Parsons the New School of Design, USA -- 6. Body: Joanne Eicher, University of Minnesota, USA -- 7. Beauty: Morag Martin, State University of New York, USA -- 8. Boundaries: Diana Crane, University of Pennsylvania, USA -- 9. Authenticity: Efrat Tseèelon, Leeds University, UK -- 10. Performance: Herbert Blau, University of Washington, USA -- 11. Dressing up: Mary Gluck, Brown University, USA -- 12. Clothing: Margaret Maynard, University of Queensland, Australia -- 13. Patronage: Nicky Ryan, University of the Arts, London, UK -- 14. Painting: Aileen Ribeiro, University of London, UK -- 15. Image: Vicki Karaminas, University of Technology, Sydney, Australia -- 16. Exhibition: Alistair O'Neil, Central St Martins, London, UK -- 17. Curatorial: Barbara Heinemann, Goldstein Museum of Design, University of Minnesota, USA.
Keywords: Fashion and art; Fashion -- History